Efforts to Resolve Waqf Disputes at the Payakumbuh Religious Court Case Number: 159/Pdt.G/2019/PA.Pyk - Mahfuzh, Hafizul; Zulfan, Zulfan; Elfia, Elfia (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
This study discusses the process of resolving a waqf dispute at the Payakumbuh Religious Court in case No. 159/Pdt.G/2019/PA.Pyk, which did not reach an agreement during the mediation stage, resulting in the lawsuit being granted. Mediation, as an important part of dispute resolution in court, aims to resolve disputes and reach a peaceful agreement between the parties. This study uses a normative legal research method. The data used in this study are secondary data, namely the decision in Case No. 159/Pdt.G/2019/PA.Pyk and legislation on waqf. To support the research, the legal materials used in this study are books, journals, and other reference sources. The data analysis used is qualitative legal analysis. The resolution of waqf disputes through mediation has legal implications for the parties, enabling them to obtain a swift decision, incur lower costs, avoid further legal proceedings, and have a decision that accommodates the interests of all parties and ensures they receive their rights fairly.